COMPARISON OF HARRY POTTER SERIES WITH RELIGION (International Journal of Food and Nutritional Sciences, 2022)
J.K. Rowling’s Harry Potter Series is a fantasy literature. It creates a great impact among children. In depth it shows the reflection of religious interpretation, when we Compare the particular book with the Bible. It questions the readers to think a lot about the comparitable. Dumbledore is a charater which replicates God and Harry Potter as Jesus christ. The Birth of Jesus is very special and it shows the salvation whereas birth of Harry potter gave the the great impact in the wizarding world, Jesus heals the sick by miracles. Whereas Harry performs magic with wands. Harry even Sacrifice his own life for the Sake of world where Jesus Sacrifices himself for the salvation of the world. In many more incidents typically shows the incorpation of The Bible in the series.